Aplicações dos conceitos e tecnologias da indústria 4.0 no transporte rodoviário de cargas no Brasil - Nascimento, José Roberto do (2022)
The production system is undergoing a digital transformation, the so-called fourth industrial revolution, or industry 4.0, which aims to improve productive means, giving more flexibility to production, allowing a greater level of customization of products and services, without this generating an increase in production. of costs. Although cargo transport is an important part of the logistics process, as it is directly linked to the production process, and needs to be prepared, computerized and using industry 4.0 concepts and technologies, there are few scientific studies related to the application of technologies. from industry 4.0 to cargo transport in Brazil. The objective of this study was to analyze the possibility of applying the concepts and technologies of industry 4.0 in road freight transport in Brazil. Through a literature review, a survey of applications of these concepts and technologies of Industry 4.0, which are being used in cargo transport in other countries, was carried out. After this survey, the field study method was used, through the application of a semi-structured interview, with 13 experts, using a form, using a Likert scale and also open questions. As a result, 19 main technologies applicable to cargo transport in Brazil were listed, being pointed out as the most applicable: (1) Monitoring of vehicles via satellite and, Automatic weighing of trailers; (2nd) Transport Management System (TMS); (3rd) Multimodal monitoring through sensors, also monitoring the internal conditions of the container; (4th) Medication distribution system with monitoring of cargo, vehicle and geographic positioning of the delivery of each cargo; (5th) RFID seals for trailers, containing vehicle, load and driver information and (6th) Driver recognition system by facial biometrics. This work contributes to theory and practice, presenting several technologies applicable to road freight transport in Brazil, based on industry 4.0, which can generate relevant improvements, both in driver safety and in cargo safety, reduce the risk of theft and accidents, as well as increased assertiveness and productivity in cargo transport, supporting technology and innovation management.